2017
DOI: 10.1038/ncomms14667
|View full text |Cite
|
Sign up to set email alerts
|

Shock-transformation of whitlockite to merrillite and the implications for meteoritic phosphate

Abstract: Meteorites represent the only samples available for study on Earth of a number of planetary bodies. The minerals within meteorites therefore hold the key to addressing numerous questions about our solar system. Of particular interest is the Ca-phosphate mineral merrillite, the anhydrous end-member of the merrillite–whitlockite solid solution series. For example, the anhydrous nature of merrillite in Martian meteorites has been interpreted as evidence of water-limited late-stage Martian melts. However, recent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 66 publications
(143 reference statements)
5
37
1
Order By: Relevance
“…The TEM observations of merrillite suggested magmatic crystallization and did not indicate any post-magmatic recrystallization (Figure 8). Merrillite does not seem to be related to another phosphate shock-transformation [17]. However, the TEM observations also revealed microstructures that were compatible with shock metamorphism.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The TEM observations of merrillite suggested magmatic crystallization and did not indicate any post-magmatic recrystallization (Figure 8). Merrillite does not seem to be related to another phosphate shock-transformation [17]. However, the TEM observations also revealed microstructures that were compatible with shock metamorphism.…”
Section: Discussionmentioning
confidence: 74%
“…Phosphates that occur in extra-terrestrial mafic rocks may provide information regarding water (volatiles) content in the environment leading to their formation and transformation (e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]). The magma source for Martian basalts is the Martian mantle; thus, the basaltic phosphates provide information on the Martian mantle composition as well as its evolution in the course of melting progression [11,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…) and it has recently been shown that this transformation can be shock‐induced (Adcock et al. ). The high‐pressure polymorph formed at an even higher compression regime is tuite (Xie et al.…”
Section: Introductionmentioning
confidence: 99%
“…, ) or merrillite formed by partially shocked whitlockite (Adcock et al. ). In fact, the slab showed other features that are characteristic of shock metamorphism, e.g., maskelynite.…”
Section: Resultsmentioning
confidence: 99%
“…Adcock et al. () tried to solve this question demonstrating that total/partial transformation from whitlockite to merrillite is possible by shock events. Consequently, in the case of the present slab, merrillite would be formed by shock events, whereas the hydrous phase was primary and directly related to latest igneous processes on Mars.…”
Section: Resultsmentioning
confidence: 99%